Mechanistic insights into acyclovir‑polyethylene glycol 20000 binary dispersions - Venkateskumar, Krishnamoorthy; Parasuraman, Subramani; Gunasunderi, Raju; Sureshkumar, Krishnan; Nayak, M. Muralidhar; Shah, Syed Adnan Ali; Kassen, Khoo; Kai, Heng Wei (International Journal of Pharmaceutical Investigation)
Objective: The objective of this study is to provide a mechanistic insight into solubility enhancement and dissolution of acyclovir (ACY) by polyethylene glycol20000 (PEG20000). Materials and Methods: Solid dispersions with differing ratios of drug (ACY) and carrier (PEG20000) were prepared and evaluated by phase solubility, in vitro release studies, kinetic analysis, in situ perfusion, and in vitro permeation studies. Solid state characterization was also done by Powder X‑Ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared spectroscopy (FT‑IR) analysis and surface morphology was assessed by Polarizing Microscopic Image (PMI) analysis, Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), and Nuclear Magnetic Resonance (NMR) analysis. Results: Thermodynamic parameters proved the solubilization effect of carrier. The aqueous solubility and dissolution of ACY were increased in all samples. Formation of solid solution, crystallinity reduction, and absence of interaction between drug and carrier was proved by XRD, DSC, and FTIR analysis. The particle size reduction and change in surface morphology were confirmed by SEM and AFM and analysis. The permeation coefficient and amount of drug diffused was higher in samples as compared to ACY. The stability was high in dispersions, and it was proved by NMR analysis. Conclusion: The mechanical insights into the enhancement of solubility and dissolution could be used as a platform to improve the aqueous solubility for other poor water soluble drugs.
Keywords: Acyclovir; crystallinity; drug–polymer miscibility; solid dispersions; solid solution